Analysis of the Knowledge Level of Breeders of Native Chickens on Nusalaut Island - Selubun, Valda Petrosina; Tulalessy, Abraham; Jesajas, Heryanus (Universitas Pattimura, 2024)
The purpose of the research was to investigate the knowledge breeders of the native chicken in Nusalaut island in relation to good native chicken production practices. Both villages and respondents were selected used purposive sampling method. The variables were knowledge of the farmers, sex, age, education, household dependency rate, length of experience and the level of income from main job. The results showed that majority (72 %) respondents attained primary school, average dependency rate 4.9 ± 1.75 persons, majority (70 %) low income, more men possessed high knowledge than women (p = 0.047), length of experience affect knowledge significantly (p=0.184) and education affect knowledge highly significantly. It was concluded that although native chicken breeders have good knowledge about chicken production in overall, but there are certain knowledge gaps on feeding and controlling diseases.